Performance of Awassi crossbred lambs in farmers flocks of semi-arid region - MAURYA, V P; NAQVI, S M K; MITTAL, J P (The Indian Journal of Animal Sciences, 2013)
A field study was conducted on 55 Awassi crossbred lambs born out of Malpurqa ewes bred artificially using freshly diluted semen of Awassi rams. Their growth and survival rates from birth to 90 days of age were compared with Malpura lambs in the farmers’ flocks of a cluster of villages around Avikanagar. Both crossbred and native lambs were kept on identical semi-intensive management throughout the period of this study. The birth weights of male and female crossbred lambs were signicantly higher than birth wrights of their counterpart Malpura lambs. The body weights of these crossbred lambs at the age 90 days were still significantly (P<0.05) higher than the respective make and female lambs of native Malpura breed. Up to 90 days of average daily gain of crossbred lambs was consistently higher than their native counter parts, sex-wise. The survival rates of crossbred and native lambs from birth to 90 days of their age was exceptionally good (100%). It is apparednt from this field study that improvement in growth and survival of Malapura sheep can be brought about by the use of Awassi rams of South-West Asia, which resemble the Malpura breed phenotypically.